2022
DOI: 10.21203/rs.3.rs-1727437/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metadichol, A natural ligand for expression of Yamanaka reprogramming factors in somatic and primary cancer cell lines

Abstract: The conversion of somatic cells back into induced pluripotent stem cells (iPSCs) or embryonic-like stem cells involves the introduction of four genes commonly called Yamanaka factors, i.e., Sox2, Oct4, Klf4, and c-Myc, into the cells. Because these genes and the viral vectors used to introduce them into cells have the potential to cause cancer, iPSC lines are not clinically useful. Most instances of direct reprogramming have achieved have been by the forced expression of defined factors using viral vectors. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this review, we provide an overview of the NRF2 signaling pathway and discuss its role in carcinogenesis.We also introduce the inhibition of NRF2 by nuclear receptors. Namani et al (21) showed that the NRF2 signaling pathway can be regulated Nuclear receptors such as RARα, RXRα, PPARγ, ERα, ERRβ, and GR inhibit Nrf2. Since these are expressed by both Stem and Fibroblasts it is not surprising that SHP is down regulated in stem cells and not expressed in Fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we provide an overview of the NRF2 signaling pathway and discuss its role in carcinogenesis.We also introduce the inhibition of NRF2 by nuclear receptors. Namani et al (21) showed that the NRF2 signaling pathway can be regulated Nuclear receptors such as RARα, RXRα, PPARγ, ERα, ERRβ, and GR inhibit Nrf2. Since these are expressed by both Stem and Fibroblasts it is not surprising that SHP is down regulated in stem cells and not expressed in Fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we presented the NRF2 signaling pathway, discussed its role in carcinogenesis, and introduced the inhibition of NRF2 by NRs. In this context, (Namani et al 2014) revealed that the NRF2 signaling pathway can be regulated and inhibited with NRs such as RARα, RXRα, PPARγ, ERα, ERRβ, and GR (Raghavan, 2022). Since these are expressed by both stem cells and broblasts, SHP is expected to be downregulated in stem cells and not expressed in broblasts.…”
Section: Discussionmentioning
confidence: 99%